(untitled) (Journal of actual problems of jurisprudence, 2017)
The article is devoted to the analysis of the formation of anti-corruption culture in foreign countries. Corruption is a global problem of the world community and a threat to modern civilization, as it hinders the normal functioning and socio-economic development of society. Corruption as a social phenomenon in any amount manifests itself in any country, exacerbating the ever growing contradictions in the relationship between civil society and the state, especially in the context of the development of market relations. Analyzing the current situation of the development of corruption in the world, one can come to the conclusion that the problem of corruption is one of the burning issues for virtually all foreign states. The article notes that corruption risks in the public service system existed and existed always and everywhere in any state. They arise simultaneously with the state and the formulation of public-political power and there are as many as the state functions. However, in different states they manifest themselves in different ways and even in the same state, at different stages of their historical development, they can have their own specific features, characteristics and causes. The study of the legislation and experience of foreign countries shows that there are a number of general principles that increase the effectiveness of activities to create an anti-corruption culture and counter corruption. Key words: corruption, legislation, anti-corruption culture, anti-corruption consciousness, anti-corruption behavior, anti-corruption strategy, anti-corruption, public service, international convention, etc.